Функціонування прецедентних феноменів в англомовному газетному дискурсі - Воротняк, Л. (Філологічний дискурс, 2018)
У статті виявлено та схарактеризовано такі основні функції
прецедентних феноменів в англомовному газетному дискурсі: функцію
характеризації, функцію експресивності, номінативну, парольну та
маніпулятивну функції. Встановлено, що функції прецедентних
феноменів увиразнюють текст та здійснюють прихований вплив на
формування думок, переконань адресата. The article identifies and describes the main functions of precedent phenomena
in the English-language newspaper discourse. It has been found that the
characterization function is mostly manifested through metaphor, comparison or
insertion structures; the function of expressiveness allows the addressee to achieve
intensification and emotionality, expresses the text due to the expressiveness of the
logical components; nominative function is carried out in order to save linguistic
resources by means of an indication of a person, a phenomenon, an event that are
significant for the recipients and do not require additional description or
explanation; the password function is a means of identifying a person with a
particular linguistic-cultural community and facilitate the integration of speakers
within this community; manipulative function of precedent phenomena – is a
function of hidden influence on the formation of opinions, beliefs and motivations of
the recipient to perform certain actions favorable to manipulator. The scientific sources devoted to the functioning of precedent phenomena are analyzed, which convincingly proves existence of different approaches to the problem
and gives grounds to assert that precedent phenomena are multifunctional. Three
main types of actualization of the function of characterization of precedent
phenomena in the newspaper discourse are distinguished: through metaphor, through comparison, through the insertion sentence.